Mask design to prevent foggy glasses and difficulty breathing - Musdah Mulia Mukmin; Hady Soedarwanto; Mega Tri Kurnia (International Journal of Public Health Science (IJPHS), 2022)
The present of the pandemic has given to a new habit that we call the new normal. One of the habits we hear most often is wearing a mask. Ironically, the use of masks creates new problems for certain populations, for example, glasses users and people with respiratory problems. Eyeglass users complain of the effect of fog on the glasses when wearing a mask, sufferers of respiratory problems complain of shortness of breath when wearing a mask. To find the design solution, the researches employed the data analysis method and experiments (trials) on the appropriate shape, structure, and material of the mask. The results of this design succeeded in presenting the expected design solutions, namely preventing the effects of eyeglasses fog, reducing the effects of tightness when wearing a mask, a display that supports appearance, and fullfil the WHO mask criteria. It presented in four basic color variants.